The Impact of Career Education on Students' Labour Market Perceptions - Chinegbonkpa Hope Nwakanma (Didaktika: Jurnal Kependidikan, 2024)
This article examines the impact of career education on students' perceptions of the labour market. The study utilized a narrative literature review methodology to investigate this topic. The article discusses how career education influences students' views on employment opportunities, skills, and employability. The findings reveal that career education plays a crucial role in equipping students with the necessary skills and knowledge to succeed in the job market. The findings underscore the significance of career education in shaping students' understanding of the labour market, career aspirations, decision-making, lifelong learning, and adaptability. The results demonstrate that career education effectively prepares students for future careers by providing accurate information, fostering essential skills, and readying them for labour market demands. It also enables students to overcome obstacles and establish networks that are vital for long-term career development. The findings highlight the importance of career education in enhancing students' employment prospects and employability. Further research is necessary to explore the impact of career education on labour market perceptions among students from diverse cultural, socioeconomic, and educational backgrounds.